Glucolipotoxicity, β-Cells, and Diabetes: The Emperor Has No Clothes - Weir, Gordon C. (Diabetes (New York, N.Y.), 2020)
Reduction of β-cell mass and function is central to the pathogenesis of type 2 diabetes. The terms glucotoxicity, lipotoxicity, and glucolipotoxicity are used to describe potentially responsible processes. The premise is that chronically elevated glucose levels are toxic to β-cells, that elevated lipid levels in the form of circulating free fatty acids (FFA) also have toxic effects, and that the combination of the two, glucolipotoxicity, is particularly harmful. Much work has shown that high concentrations of FFA can be very damaging to β-cells when used for in vitro experiments, and when infused in large amounts in humans and rodents they produce suppression of insulin secretion. The purpose of this Perspective is to raise doubts about whether the FFA levels found in real-life situations are ever high enough to cause problems. Evidence supporting the importance of glucotoxicity is strong because there is such a tight correlation between defective insulin secretion and rising glucose levels. However, there is virtually no convincing evidence that the alterations in FFA levels occurring during progression to diabetes are pathogenic. Thus, the terms lipotoxicity and glucolipotoxicity should be used with great caution, if at all, because evidence supporting their importance has not yet emerged.